ANALYSIS OF HIGH SCHOOL STUDENTS’ NUMERACY LITERACY SKILLS ON POLYNOMIAL TOPICS VIEWED FROM A GENDER PERSPECTIVE - Putri, Taqiyyah Nabila; Tania, Nabilla Syalita; Soraya, Hanifah (Fakultas Keguruan dan Ilmu pendidikan (FKIP) Universitas Labuhan Batu, 2025)
This study aims to analyze high school students’ numeracy literacy skills on polynomial material by considering gender differences as one of the factors that may influence variations in students’ ways of thinking. The research subjects were randomly selected from Grade XII students at SMA Negeri 1 Percut Sei Tuan and examined through a numeracy literacy test and structured interviews designed to explore their understanding of context, accuracy and completeness of computational procedures, and ability to interpret the mathematical meaning of the results obtained. Data analysis was carried out through the stages of data reduction, data display, and conclusion drawing following qualitative analysis procedures. The findings indicate a tendency for differences in performance patterns between male and female students. Female students appeared more systematic in explaining mathematical reasoning, better at connecting computational results with the conceptual meaning of polynomials, and more consistent in interpreting information. In contrast, male students demonstrated strengths in procedural aspects, particularly accuracy and speed in performing calculations, although their explanations of deeper mathematical meaning tended to be less consistent. These findings illustrate that gender differences may contribute to variations in numeracy literacy skills, and the results can serve as a basis for teachers in designing learning approaches that are more responsive to students’ thinking characteristics.